La reinvención del Museo Nacional de Prado: De arte monomedia a experiencia museística transmedial - Venditti, Stephanie (Folios, revista de la Facultad de Comunicaciones y Filología, 2023)
The case of the Museo Nacional del Prado, in Spain, innovates with a proposal that seeks to modernize its image and democratize its valuable and artistic contents. This paper aims to explore how the Museum turns its richest collection to multiple platforms, achieving not only a multiplicity of content but also the participation of users in a little explored area. This purpose, to develop a physical and virtual navigation, allows consumers to feedback in an intuitive way as a bridge that connects them with culture